The thermal structure of troposphere, stratosphere and mesosphere over the equatorial India (MAUSAM, 1980)
The thermal structure of the equatorial troposphere, stratosphere and mesosphere has been constructed baked on the M-100 meteorological rocket sounding data at Thumba ( 8° 32' N, 76° 52' E ). The upper air rocket temperature profile shows short and long term periodic variations. The Thumba actual temperature profile is found to be in good agreement within 2° C with the CIRA Model 1972 for 10 ° N in the stratosphere, but mesospheric temperatures over Thumba are lower by about '5 to 25° C. The results of harmonic analysis, lapse rate, sporadic warming are discussed, highlighting the characteristics of equatorial tropopause, stratopause and mesopause.